Effect of Magnetic Field Induce Arc in Autogenous TIG Welding of 304 Stainless Steel Butt Joint - Haikal Haikal; Moch. Chamim; Deni Andriyansyah; Emanuel Budi Raharjo; Ario Sunar Baskoro; Isnarno Isnarno (Automotive Experiences, 2021)
This paper reports the use of External Magnetic Field-Tungsten Inert Gas (EMF-TIG) method in butt joint applications to determine the effect of welding arc compression on the quality of butt joint of SS 304 thin plate was reported. The welding process was performed without using filler or autogenous welds. The external magnetic field was generated by placing a magnetic solenoid around the TIG welding torch. The results of this study showed that EMF-TIG welding can produce a more uniform bead width along the weld line compare with conventional TIG. Moreover, the D/W ratio obtained under external magnetic field was higher than without magnetic. However, the tensile strength of butt joint decreased with EMF-TIG because there is constriction in arc welding which produces shrinkage weld pool volume. In addition, high welding speeds result in a decrease in the tensile strength of both conventional TIG and EMF-TIG welds.